Distribución de metales en el acíbar de hojas de zábila (Aloe vera (L). Burm.f.) - Carlos E. Rondón; Oswaldo Saavedra* (Avances en Química, 2008)
This work presents the distribution of Na, Ca, Mg, K, Cu, Zn, Mn and Fe in Aloe vera leaves exudate by flame atomic absorption spectrometry (FAAS) and Cr by electrothermal atomic absorption spectrometry (ETAAS). The plants were cultivated in the city of Coro, Falcón state. The samples were collected from internal, medium and external leaves. The accuracy of the method was evaluated using a certified reference material NBS 1572. The average precision was 1.39%. The applied method was accurate, precise and free from interferences.